Pig slurry as a nutrient source in wheat/corn succession - Bison Pinto, Marlo Adriano; Basso, Claudir José; Santi, Antônio Luis; Sailva, Rodrigo Ferreira da; Silva, Dieson Ruy Orsolin da (Revista Ceres, 2016)
Wheat and corn are important grains in the agricultural scenario of Brazil, which demands adequate supply of nutrients, particularly nitrogen, in crop succession. The use of pig slurry (PS) as a full and/or partial alternative to mineral fertilization in crop areas has been identified as an important alternative for the disposal of this waste. Therefore, the objective of this study was to evaluate the utilization of PS as fertilizer in wheat/corn succession under some plant parameters and grain yield. The experiment was conducted under field in randomized block design with four replications and five treatments, three with PS (40, 80, 160 m³ ha-1) and two controls (no fertilization and mineral NPK fertilization), which were applied manually on the soil shortly after the sowing of crops. The application of PS proved to be a significant source of nutrients in wheat/corn succession. For grain yield, even with no significant difference between treatments, when compared to the treatment without fertilizer, the application of 80 m3 ha-1 increased wheat and corn yield in 23% and 10%, respectively. In comparison to NPK fertilization, this increase was only of 5.4% and 4.7% for wheat and corn, respectively. PS is an efficient alternative and it can be used as the source of these nutrients in wheat/corn succession, and the use of 80 m3 ha-1 provides satisfactory results for all evaluated variables.